The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.3906/tar-1402-27
|View full text |Cite
|
Sign up to set email alerts
|

Distribution, occurrence of cry genes, and lepidopteran toxicity of native Bacillus thuringiensis isolated from fig tree environments in Aydın Province

Abstract: Bacillus thuringiensis (Bt) has a significant impact on biological pest control because of the insecticidal activity through its parasporal inclusion bodies (crystal proteins). Fig is an economically important plant in Turkey; agricultural pests result in a considerable economic loss in fig quality and cultivation. The aim of this work was to isolate, characterize, and determine the lepidopteran toxicity of Bt obtained from fig groves in Aydın Province. A total of 606 colonies (out of 1167) obtained from 380 s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
13
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 39 publications
4
13
0
1
Order By: Relevance
“…In fact, we showed that the strains 13 MY and 42 MY contain cry1 gene different from that of B. thuringiensis subsp. kurstaki in our previous study (Alper et al, 2014). Similarly, partial DNA sequence analysis of cry2A genes was different from that of the reference strain according to phylogenetic tree in this present study.…”
Section: Discussionmentioning
confidence: 75%
See 3 more Smart Citations
“…In fact, we showed that the strains 13 MY and 42 MY contain cry1 gene different from that of B. thuringiensis subsp. kurstaki in our previous study (Alper et al, 2014). Similarly, partial DNA sequence analysis of cry2A genes was different from that of the reference strain according to phylogenetic tree in this present study.…”
Section: Discussionmentioning
confidence: 75%
“…Profiles of cry genes of the strains were identified previously (Alper et al, 2014) and are presented in Table 2. …”
Section: Profiles Of Cry Genes Of Bacillus Thuringiensis Strainsmentioning
confidence: 99%
See 2 more Smart Citations
“…According to Alper et al (2014), some strains that harbour the same genes may not be as effective as other toxic strains that have those same genes, indicating that these genes could be poorly expressed because of a weak promoter in the strains. Thus, poor expression of the cry genes in the BR78 and S1302 isolates could explain the cry genes in the genetic profile but not in the protein profile.…”
Section: Discussionmentioning
confidence: 99%